Book Review: Tourism Planning: Policies, Processes and Relationships by C. Michael Hall. (16th February 2010) - Joppe, Marion
Tourism Planning: Policies, Processes and Relationships, by C. Michael Hall. 2nd ed. Harlow, Pearson Education, 2008. 302 pp. ISBN-13: 978-0-13-204652-7